Personalities and relationship of the dog-handler dyad in animal assisted interventions: An exploratory correlational study - Marta De Santis; Luca Martelli; Alberto Mair; Diletta Fornasiero; Lorena Filugelli; Emma Bassan; Margherita Soncin; Franco Mutinelli; Laura Contalbrigo (Applied Animal Behaviour Science, 2026)

Human-Animal Adoption: Bioethical Challenges and Considerations - Luisa Bellissimo; Emma Bassan; Franco Manti; Simona Normando; Franco Mutinelli; Laura Contalbrigo (Biosemiotics, 2025)

Evaluating the personality of dogs involved in animal-assisted interventions and their relationship with the handler: the Italian landscape - Alberto Mair; Luca Martelli; Marta De Santis; Diletta Fornasiero; Lorena Filugelli; Simona Normando; Franco Mutinelli; Laura Contalbrigo (Applied Animal Behaviour Science, 2025)

Spatial clusters of Varroa destructor control strategies in Europe - Robert Brodschneider; Johannes Schlagbauer; Iliyana Arakelyan; Alexis Ballis; Jan Brus; Valters Brusbardis; Luis Cadahía; Jean-Daniel Charrière; Robert Chlebo; Mary F. Coffey; Bram Cornelissen; Cristina Amaro da Costa; et al. (Journal of Pest Science, 2023)
Beekeepers have various options to control the parasitic mite Varroa destructor in honey bee colonies, but no empirical data are available on the methods they apply in practice. We surveyed 28,409 beekeepers maintaining 507,641 colonies in 30 European countries concerning Varroa control methods. The set of 19 different Varroa diagnosis and control measures was taken from the annual COLOSS questionnaire on honey bee colony losses. The most frequent activities were monitoring of Varroa infestations, drone brood removal, various oxalic acid applications and formic acid applications. Correspondence analysis and hierarchical clustering on principal components showed that six Varroa control options (not necessarily the most used ones) significantly contribute to defining three distinctive clusters of countries in terms of Varroa control in Europe. Cluster I (eight Western European countries) is characterized by use of amitraz strips. Cluster II comprises 15 countries from Scandinavia, the Baltics, and Central-Southern Europe. This cluster is characterized by long-term formic acid treatments. Cluster III is characterized by dominant usage of amitraz fumigation and formed by seven Eastern European countries. The median number of different treatments applied per beekeeper was lowest in cluster III. Based on estimation of colony numbers in included countries, we extrapolated the proportions of colonies treated with different methods in Europe. This suggests that circa 62% of colonies in Europe are treated with amitraz, followed by oxalic acid for the next largest percentage of colonies. We discuss possible factors determining the choice of Varroa control measures in the different clusters.

Recent confirmation of a single haplotype in the Italian population of Vespa velutina - Anna Granato; Enrico Negrisolo; Jessica Bonomi; Laura Zulian; Federico Cappa; Laura Bortolotti; Franco Mutinelli (Biological Invasions, 2019)

How to slow the global spread of small hive beetles, Aethina tumida - Marc Oliver Schäfer; Ilaria Cardaio; Giovanni Cilia; Bram Cornelissen; Karl Crailsheim; Giovanni Formato; Akinwande Kayode Lawrence; Yves Le Conte; Franco Mutinelli; Antonio Nanetti; Jorge Rivera-Gomis; Anneke Teepe; et al. (Biological Invasions, 2019)

Immunohistochemistry by anti-cleaved-Lamin A: an improved approach to tackle the misuse of glucocorticoids in cattle - Claudia Zanardello; Marzia Pezzolato; Katia Capello; Mario Botta; Elisa Baioni; Franco Mutinelli; Marta Vascellari; Elena Bozzetta (Food Additives & Contaminants: Part A, 2018)

Retrospective evaluation of lead contamination in honey from 2005 to present in northeastern Italy and future perspectives in the light of updated legislation - Marianna Martinello; Nicoletta Dainese; Chiara Manzinello; Alice Borin; Albino Gallina; Franco Mutinelli (Food Additives & Contaminants Part B-Surveillance, 2016)

First report in Italy of the dusky sap beetle, Carpophilus lugubris, a new potential pest for Europe - Francesca Marini; Franco Mutinelli; Fabrizio Montarsi; Andrew Richard Cline; Enzo Gatti; Paolo Audisio (Journal of Pest Science, 2013)

Adjuvants and delivery systems in veterinary vaccinology: current state and future developments - Peter M. H. Heegaard; Laurence Dedieu; Nicholas Johnson; Marie-Frédérique Le Potier; Michael Mockey; Franco Mutinelli; Thomas Vahlenkamp; Marta Vascellari; Nanna Skall Sørensen (Archives of Virology, 2011)

Use of an Area Index to Retrospectively Analyze the Elimination of Fox Rabies in European Countries - Thomas Selhorst; Thomas Müller; Heinzpeter Schwermer; Mario Ziller; Hartmut Schlüter; Urs Breitenmoser; Uli Müller; Bernard Brochier; Paul-Pierre Pastoret; Franco Mutinelli (Environmental Management, 2005)